2018
DOI: 10.3389/fneur.2018.00637
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke BDNF Concentration Changes Following Physical Exercise: A Systematic Review

Abstract: Background: Research over the last two decades has highlighted the critical role of Brain-derived neurotrophic factor (BDNF) in brain neuroplasticity. Studies suggest that physical exercise may have a positive impact on the release of BDNF and therefore, brain plasticity. These results in animal and human studies have potential implications for the recovery from damage to the brain and for interventions that aim to facilitate neuroplasticity and, therefore, the rehabilitation process.Purpose: The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 46 publications
(76 reference statements)
0
37
0
6
Order By: Relevance
“…In addition to administration of therapeutic agents and manipulation of gene expression, physical exercise was also capable of promoting BDNF expression and improving the neurological outcome after experimental stroke (reviewed by Alcantara et al [72]). Ke et al claimed that voluntary exercise is correlated with an increase in hippocampal BDNF levels and functional recovery [73].…”
Section: Bdnf Facilitates Functional Recovery In Poststrokementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to administration of therapeutic agents and manipulation of gene expression, physical exercise was also capable of promoting BDNF expression and improving the neurological outcome after experimental stroke (reviewed by Alcantara et al [72]). Ke et al claimed that voluntary exercise is correlated with an increase in hippocampal BDNF levels and functional recovery [73].…”
Section: Bdnf Facilitates Functional Recovery In Poststrokementioning
confidence: 99%
“…In previous studies using rat ischemia models, it was found that when BDNF synthesis was blocked, the beneficial effects on the recovery of skilled reaching were mostly negated [79], while intravenous administration of BDNF significantly enhanced the functional motor recovery of the treated rats, compared to the untreated controls [80,81]. Behavioral and physical therapies, such as aerobic/physical exercise, transcranial direct current stimulation (tDCS), and extremely lowfrequency electromagnetic field therapy (ELF-EMF), were all found to increase the blood and/or brain levels of BDNF [72,77,[82][83][84][85]. In addition, BDNF-mediated learning memory may also be partially involved in the poststroke rehabilitation of motor function and language relearning [86-88].…”
Section: Bdnf Induces Neuroplasticity In Poststroke Rehabilitationmentioning
confidence: 99%
“…Intracerebroventricular and intravenous infusion of BDNF increases the number of pyramidal cells in CA1, reduces the infarct volume, and promotes motor improvements 18 . The effects of physical exercise seem analogous to the effects of selective serotonin reuptake inhibitors, and rodent models support that physical exercise increases the hippocampal levels of BDNF 19,20 .…”
Section: Introductionmentioning
confidence: 85%
“…Improvements in motor skill learning and memory induced by aerobic exercise have been associated with increased peripheral blood concentrations of brain‐derived neurotrophic factor (BDNF) (McDonnell, Buckley, Opie, Ridding, & Semmler, ). Aerobic exercise increases BDNF (Alcantara et al, ; Skriver et al, ), which is involved with neurogenesis (Skriver et al, ) and neuroprotection (Schäbitz, Schwab, Spranger, & Hacke, ), thereby playing an important role in stroke recovery, including facilitating functional upper limb motor rehabilitation (Schäbitz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic exercise increases BDNF (Alcantara et al, 2018;Skriver et al, 2014), which is involved with neurogenesis (Skriver et al, 2014) and neuroprotection (Schäbitz, Schwab, Spranger, & Hacke, 1997), thereby playing an important role in stroke recovery, including facilitating functional upper limb motor rehabilitation (Schäbitz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%